The state of operational technology security. Issue 10 (October 2019) - Mansfield-Devine, Steve
Abstract : It's a sad and worrying fact that awareness about cyber security – and subsequent action – has lagged behind as technology has progressed. This is true in every domain, but perhaps none more so than operational technology (OT). The systems used to run manufacturing plants, control power stations and water utilities and manage countless industrial processes – with many of the installations being deemed critical national infrastructure (CNI) because of their importance to safety, daily life and a country's economy – have often been left poorly protected from cyber attacks. In this interview, Tim Ennis and David Gray of NTT Security discuss the state of OT security and what can be done about it. This is particularly true with operational technology (OT). The systems used to run manufacturing plants, control power stations and water utilities, as well as manage countless industrial processes, have often been left poorly protected from cyber attacks. In this interview, Tim Ennis and David Gray of NTT Security discuss the state of OT security and what can be done about it.